The Fermentation of Robusta Coffee With Termite Enzymes to Improve Quality and Taste - Sudarma, I Wayan; Badung S.D, A.A.N. (KnE Life Sciences, 2022)
This research involved the fermentation of robusta coffee with termite enzymes in Subak Pura Pengulu, Bongancina village, Busungbiu–Buleleng between May and December 2019. The raw materials included red pickled coffee, termite microbes, water, pH meter molasses and plastic. 100 kg of the coffee sample was added in each wet processing treatment. Methods included sample preparation, field observations, coffee harvesting, sorting, and post-harvest processing. A completely randomized design with four treatments and five replications was used to create high-quality products with distinct flavors and aromas. Physical quality, taste, caffeine content and amino acids were reported. According to the findings, the yields of wet coffee beans and dry samples without skin (ose) were 51.73% and 19.36%, respectively. In addition, in the specialty categories, the three-day fermentation period produced the best taste, with a score of 83.50. Furthermore, the defect value was specified as 13.4, water content as 12.5, caffeine content as 3.40% w/w, and the acids, including oleic and α-linoleic, were 51.147 and 0.587 ppm, respectively. According to the economic estimations, the three-day fermented coffee would produce an optimal profit of IDR 8,090,000. Keywords: robusta coffee, termite, fermentation